William Godwin : a political life - Thomas, Richard Gough (London : Pluto Press, 2019)
A biography of the early anarchist whose life and work was at the heart of British Radicalism.
Cover; Contents; Series Preface; Acknowledgements; 1. Introduction: The Anarchist; 2. The Minister: 1756-93; 3. The Philosopher: 1793; 4. The Activists: 1794-95; 5. The Husband: 1796-99; 6. The Educator: 1800-09; 7. The Father: 1810-19; 8. The Pensioner: 1819-36; 9. The Legacy; Notes; Bibliography; Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 21, 2019).
JSTOR
Keywords: Godwin, William, -- 1756-1836 -- Philosophy; Godwin, William, -- 1756-1836; Anarchistes -- Grande-Bretagne -- Biographies; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Philosophy; Biographies; Biographies; Biographies